Angle Kappa is Not Correlated with Patient-Reported Outcomes After Multifocal Lens Implantation - Liu X; Hannan SJ; Schallhorn SC; Schallhorn JM (Clinical Ophthalmology, 2024)
Xi Liu,1,2 Stephen J Hannan,3 Steven C Schallhorn,4,5 Julie M Schallhorn5,6 1Southwest Hospital/Southwest Eye Hospital, Third Military Medical University (Army Military Medical University), Chongqing, People’s Republic of China; 2Key Laboratory of Visual Damage and Regeneration & Restoration in Chongqing, Chongqing, People’s Republic of China; 3Optical Express, Glasgow, UK; 4Carl Zeiss Meditec, Dublin, CA, USA; 5Department of Ophthalmology, University of California, San Francisco, San Francisco, CA, USA; 6Francis I. Proctor Foundation, University of California United States, San Francisco, CA, USACorrespondence: Julie M Schallhorn, Francis I. Proctor Foundation, University of California, 490 Illinois St, San Francisco, CA, USA, Tel +1 415-514-1922, Email Julie.schallhorn@ucsf.eduPurpose: To examine the effect of preoperative angle kappa on patient-reported outcomes after multifocal lens placement during cataract surgery and determine if it is an effective measure for preoperative patients screening for multifocal lens placement.Setting: Private refractive surgery clinics.Design: Retrospective cohort study.Methods: All patients undergoing bilateral cataract or refractive lens exchange surgery with a target of emmetropia between 2013 and 2017 at Optical Express (Glasgow, UK) with multifocal lens placement for whom preoperative angle kappa measurement and a postoperative month 1 patient-reported outcomes measures were available were included.Results: A total of 1368 patients were identified. Median preoperative angle kappa was 0.41mm with an interquartile range of 0.30mm to 0.53mm. Preoperative angle kappa did not have a significant association with patient-reported satisfaction with vision (correlation coefficient 0.15, 95% confidence interval − 0.081 to 0.39, P = 0.20) nor with patient-reported photic phenomena (P > 0.09 for all comparisons). A receiver-operator characteristic analysis did not yield a viable cutoff predictive of patient-reported satisfaction.Conclusion: Angle kappa was not predictive of patient-reported satisfaction in this study. This study did not find evidence that it should be used as a screening test for patients considering multifocal intraocular lens placement.Keywords: angle kappa, multifocal intraocular lens, refractive lens exchange